PENGARUH LATIHAN KETERAMPILAN SOSIAL TERHADAP PENINGKATAN KEMAMPUAN SOSIALISASI ANAK DENGAN ATTENTION DEFISIT HYPERACTIVITY DISORDER (ADHD) - Yeni Suryaningsih (The Indonesian Journal of Health Science, 2017)
Attention deficit hyperactivity disorder (ADHD) is a neurobehavioral disorder that most often occurs in children, which is also a chronic condition that most often affects children of school age, and is a mental disorder common in children ages 3- 5 years. Without proper treatment can be chronic depression. Social skills training is a way given to children who have difficulty interacting disorder. The goal is to improve a person's ability to interact in an environment. This exercise can improve interpersonal skills with socializing train. This study is a non-randomized quasi-experimental one-group pretest-posttest design. This research was conducted in kindergarten Dahlia Jember. Total sample 7 sample with purposive sampling technique. Variables - variables of the study consisted of social skills training, attention deficit hyperactivity disorder comprises.       Results of the study Analysis of the difference highest increase was 26 and the lowest difference has a value of 20. Analysis Wilcoxon (α 0.05) p = 0.016. Conclusions social skills training can be done to improve the social skills of children with ADHD. This research is expected to contribute or contribute to the development of science and its applications, especially in the field of children with psychiatric problems.